Membership Management System for St. John Ambulance of Malaysia SMK Jalan Pasir Puteh (SJMS) - Wong, Lik; Sulaiman, Rabatul Aduni (Applied Information Technology And Computer Science, 2025)
The Membership Management System for St. John Ambulance of Malaysia SMK Jalan Pasir Puteh (SJMS) is a web-based platform tailored to address the administrative needs of St. John Ambulance of Malaysia SMK Jalan Pasir Puteh (SJAM SMKJPP). The current manual system for tracking member details, certifications, and activities is inefficient, prone to errors, and lacks centralised access. The project aims to design, develop, and test the SJMS, leveraging the Prototyping Software Development Lifecycle (SDLC) model to ensure iterative feedback from stakeholders. The system incorporates modules such as login, register, profile management, activity management, badge management, reporting, and learning materials, and it is designed for different user roles (super admin, admins, and members). With deployment targeted for SJAM SMKJPP in Ipoh, Perak, SJMS enables real-time data access and streamlined management tasks. As a result, the system successfully enhances task automation, improves data accuracy, and simplifies member tracking and reporting. Its implementation is significant in transforming manual processes into a centralized digital system, ultimately supporting better decision-making and promoting a more efficient, transparent, and engaging administrative environment.